Using fractal dimension as discriminator of infected HeLa cells from spectrophotometric images. (15th May 2008) - Dobrescu, Radu; Ichim, Loretta
The paper presents an original experimental optical method to characterise, using fractal dimension, cell nuclei size distribution for virus-infected and non infected cells. Here is described the solution to design an optical system, which allow backscattering Mie diffusion spectra determination for biological sample on transparent holder. Fractal dimension as interest area of Mie scattering spectra was computed using a software package, which can store and process recorded data. The results indicate obviously higher values of fractal dimension for HSV-infected biological samples when compared with non-infected biological samples. This allows us to clearly discriminate between virus-infected and non-infected biological samples.